Towards in situ continuous feeding via controlled release of complete nutrients for fed-batch culture of animal cells - Rawat, Jyoti; Gadgil, Mugdha (Biochemical Engineering Journal, 2020)
Small-scale culture of animal cells in suspension is of importance for many applications. At a small-scale, fed-batch is achieved either by manual bolus feeding or the use of liquid handling robots. In this study, we report an alternate application of a hydrogel for in situ continuous delivery of a nutrient feed comprising 18 amino acids, vitamins, antioxidants, and trace elements. We show that amino acid release is sustained for at least seven days. Importantly, release rates of individual amino acids can be independently modulated by changing their loading. We demonstrate the application of this hydrogel for complete in situ feeding of nutrients to a suspension adapted CHO cell line expressing IgG leading to 2.7-fold and 4-fold improvement in integral viable cell density (IVCD) and volumetric productivity respectively. This is similar to improvements obtained by bolus liquid feeding. Further, supplying glucose from the same hydrogel to eliminate manual feeding led to a 1.8-fold increase in IVCD accompanied by a 3-fold increase in volumetric productivity as compared to batch culture. In summary, this study provides a proof-of-concept that hydrogels can enable completely closed in situ feeding for mammalian cell culture requiring no external intervention. Such continuous in situ delivery can potentially enable closed culture systems maintaining nutrients at low levels mimicking physiological concentrations.
Keywords: Amino acids; CHO cells; Closed system; Fed-batch; Hydrogel for continuous feeding; In situ nutrient release